Molecular Identification of Fungi - Gherbawy, Youssuf; Voigt, Kerstin; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
Fungi enjoy great popularity in pharmaceutical, agricultural, and biotechnological applications. Recent advances in the decipherment of whole fungal genomes promise an acceleration of these trends. This timely book links scientists from different parts of the world who are interested in the molecular identification of fungi combined with the exploration of the fungal biodiversity in different ecosystems. It provides a compendium for scientists who rely on a rapid and reliable detection of fungal specimens in environmental as well as clinical resources in order to ensure the benefit of industrial and clinical applications. Chapters focus on the opportunities and limits of the molecular marker-mediated identification of fungi. Various methods, procedures and strategies are outlined. Furthermore, the book offers an update of the current progress in the development of fungal molecular techniques, and draws attention to potential and associated problems, as well as integrating theory and practice.
Plant Pathological and Environmental Biological Aspects -- Fungal Pathogens of Plants in the Homogocene -- Molecular Techniques for Classification and Diagnosis of Plant Pathogenic Oomycota -- Plasmodiophorids: The Challenge to Understand Soil-Borne, Obligate Biotrophs with a Multiphasic Life Cycle -- Applications of Molecular Markers and DNA Sequences in Identifying Fungal Pathogens of Cool Season Grain Legumes -- Quantitative Detection of Fungi by Molecular Methods: A Case Study on Fusarium -- DNA-Based Tools for the Detection of Fusarium spp. Pathogenic on Maize -- Molecular Detection and Identification of Fusarium oxysporum -- Molecular Chemotyping of Fusarium graminearum, F. culmorum, and F. cerealis Isolates From Finland and Russia -- Molecular Characterization and Diagnosis of Macrophomina phaseolina: A Charcoal Rot Fungus -- Molecular Diagnosis of Ochratoxigenic Fungi -- Molecular Barcoding of Microscopic Fungi with Emphasis on the Mucoralean Genera Mucor and Rhizopus -- Advances in Detection and Identification of Wood Rotting Fungi in Timber and Standing Trees -- Molecular Diversity and Identification of Endophytic Fungi -- Molecular Identification of Anaerobic Rumen Fungi -- Human Pathological and Clinical Aspects -- New Approaches in Fungal DNA Preparation from Whole Blood and Subsequent Pathogen Detection Via Multiplex PCR -- Classification of Yeasts of the Genus Malassezia by Sequencing of the ITS and D1/D2 Regions of DNA -- DNA-Based Detection of Human Pathogenic Fungi: Dermatophytes, Opportunists, and Causative Agents of Deep Mycoses -- Applications of Loop-Mediated Isothermal Amplificaton Methods (LAMP) for Identification and Diagnosis of Mycotic Diseases: Paracoccidioidomycosis and Ochroconis gallopava infection -- Identification of the Genus Absidia (Mucorales, Zygomycetes): A Comprehensive Taxonomic Revision -- Molecular Characters of Zygomycetous Fungi.
Keywords: Life sciences; Microbiology; Microbial ecology; Plant diseases; Entomology; Cytology -- Research_xMethodology.; Life Sciences; Fungus Genetics; Biological Techniques; Eukaryotic Microbiology; Medical Microbiology; Plant Pathology; Microbial Ecology